Low-cost three-phase self-excited induction generator for supplying isolated single-phase loads. (19th January 2021) - Benhacine, Tarek Zine-eddine; Nesba, Ali; Mekhtoub, Said; Ibtiouen, Rachid
This paper deals with the three-phase self-excited induction generator (SEIG) used as a low-cost electrical generator for supplying isolated single-phase loads. This operating mode causes an extreme unbalance in the generator. To solve this problem, a new control method is proposed in order to allow the SEIG to operate under balanced conditions and tracks a desired voltage. The proposed control method is based on the adjustment of the value of the excitation capacitors connected to the SEIG, where a switched capacitors system is proposed for this purpose. The required values of the excitation capacitors are calculated from the numerical resolution of the steady-state model equations of the SEIG by using an optimisation algorithm. An experimental prototype based on electromagnetic relays and an Arduino board is built and tested. The experimental validation is performed on a three-phase 1.5 kW SEIG.